NIST CSF-2.0 Compliant GPU Shader Execution - Lungu, Nelson; Al Rababah, Ahmad Abdulqadir; Dash, Bibhuti Bhusan; Syed, Asif Hassan; Barik, Lalbihari; Rout, Suchismita; Tembo, Simon; Lubobya, Charles; Patra, Sudhansu Shekhar (Engineering, Technology & Applied Science Research, 2024)
This article introduces a mechanism for ensuring trusted GPU shader execution that adheres to the NIST Cybersecurity Framework (CSF) 2.0 standard. The CSF is a set of best practices for reducing cybersecurity risks. We focus on the CSF’s identification, protection, detection, and response mechanisms for GPU-specific security. To this end, we exploit recent advancements in side-channel analysis and hardware-assisted security for the real-time and introspective monitoring of shader execution. We prototype our solution and measure its performance across different GPU platforms. The evaluation results demonstrate the effectiveness of the proposed mechanism in detecting anomalous shader behaviors that only incur modest overhead at runtime. Integrating the CSF 2.0 principles into the proposed GPU shader pipeline leads to an organizational recipe for securing heterogeneous computing resources.